Digitally-Assisted conventional immediate denture in aggressive periodontitis with limited abutments - Utari Kresnoadi; Hendri B. Gunawan (Indonesian Journal of Prosthodontic, 2025)
Aggressive Periodontitis (AgP) frequently precipitates premature, multi-unit tooth loss in young adults, imposing substantial esthetic and psychological burdens. While the immediate provision of a prosthesis is critical to preclude the damaging edentulous phase and sustain patient confidence, conventional impression techniques inherently pose a significant risk of iatrogenic trauma to the remaining, often highly mobile, fragile abutments. This report details a hybrid digital-conventional protocol designed to maximize clinical safety and esthetic predictability during immediate removable partial denture (IRPD) delivery amidst fragile abutments. A 35-year-old female diagnosed with generalized AgP necessitated the extraction of eleven teeth, with only periodontally sound canines and premolars retained. Intraoral scanning technology was strategically utilized for anatomical data acquisition, successfully mitigating the risk of inadvertent dislodgment of the mobile abutments. The resulting digital data facilitated a precise pre-extraction simulation of the final ridge contour and esthetic try-in, guiding the subsequent conventional laboratory fabrication. An acrylic IRPD was delivered immediately post-extraction, successfully resolving the pre-existing diastema and restoring patient function. The strategic integration of intraoral scanning into a conventional IRPD workflow offers a cost-effective, clinically safe, and highly predictable solution for managing complex immediate prosthetic cases involving limited and compromised supporting structures, thereby enhancing treatment outcomes. Keywords Aggressive Periodontitis; Immediate Denture; Intraoral Scanning; Hybrid Workflow; Compromised Abutments.